Idealist theories of sport in relation to art - Danny Shorkend (Journal of Aesthetics & Culture, 2018)
If what can be described as “ideal” in relation to art may be somewhat abstract, then in this article I will apply the basic notion that the ideal is that which links the invisible (thought-content) and visible (the form, “frame”, “vessel”) to that of ideal as it manifests in sport. For, since we cannot speak intelligibly about x without some image or word, sport “pictures” or shows are an ideal in specific forms, some of which is certainly artistic, rendering a watered-down version of the ideal (abstract), though no less a reflection thereof. In such terms, it is not that sport is “lower” than art; rather it concretizes the abstract in a less intellectual format though no less powerfully and meaningfully. It draws from art and spreads its message downward, as a material framing device of the ideal that satisfies not only a need to relate and socialize, but an intuitive grasp of the hope for a better, more ideal existence. In these respects, sport like art necessarily has moral implications which will be developed toward the close of the article with a view to determining the manner in which the ideal shapes both sport (and art).